Functions (and Consequences) of Selected Paratexts in Editions of Grimms’ Fairy Tales Published in 2000–2021: Prolegomenon - Kowalczyk, Kamila (Porównania, 2023)
This article focuses on representative paratexts accompanying Polish language editions in fairy tales from Jacob and Wilhelm Grimms’ selection published in the Polish market in 2000-2021. On a basis of, among others, forewords, afterwords, blurbs, information included in prelims, and colophons, an attempt was made to signal research problems concerning the cultural status of Grimms' Fairy Tale emerging from paratexts. A particular attention was paid to communication strategies of editors, publishers and translators, as well as to potential receiving consequences of elements surrounding and supplementing the actual text of a tale.